âPembuatan Isolat Protein Ikan (IsPI) dari ikan Tongkol dengan Metode Pergantian pH Perlakuan Alkaliâ - , BAGUS KELANA, Prof. Ir. Ustadi, M.P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to know effect of pH Shift process of Fish Protein Isolate (FPI) Tongkol functional characteristic. FPI Tongkol compared with Surimi which maded from conventional methods, to understand effect of this treatment. The research used pH 10.5, 11 and 11.5 treatment (Alkaline process) on the protein dissolved process. The results are FPI Tongkol have significant different (P<0.05) of treatment concerning Conventional Surimi. pH 11 treatment have Yield score, Moisture content, Lipid content, Protein content, Salt-soluble Protein content and Water holding capacity are 72.66%, 76.24%, 1.66%, 70.33%, 66.86%, 83.90%, respectively.